Early-stage adenocarcinoma of the esophagus with mid to deep submucosal invasion (pT1b sm2-3): the frequency of lymph-node metastasis depends on macroscopic and histological risk patterns - Manner, Hendrik; Lorenz, Dietmar (Diseases of the esophagus, 2017)
The rate of lymph-node (LN) metastasis in early adenocarcinoma (EAC) of the esophagus with mid to deep submucosal invasion (pT1b sm2/3) has not yet been precisely defined. The aim of the this study was to evaluate the rate of LN metastasis in pT1b sm2/3 EAC depending on macroscopic and histological risk patterns to find out whether there may also be options for endoscopic therapy as in cancers limited to the mucosa and the upper third of the submucosa. A total of 1.718 pt with suspicion of EAC were referred for endoscopic treatment (ET) to the Dept. of Internal Medicine II at HSK Wiesbaden 1996–2010. In 230/1.718 pt, the suspicion (endoscopic ultrasound, EUS) or definitive diagnosis of pT1b EAC (ER/surgery) was made. Of these, 38 pt had sm2 lesions, and 69 sm3. Rate of LN metastasis was analyzed depending on risk patterns: histologically low-risk (hisLR): G1-2, L0, V0; histologically high-risk (hisHR): ≥1 criterion not fulfilled; macroscopically low-risk (macLR): gross tumor type I-II, tumor size ≤2 cm; macroscopically high-risk (macHR): ≥1 criterion not fulfilled; combined low-risk (combLR): hisLR+macLR; combined high-risk (combHR): at least 1 risk factor. LN rate was only evaluated in pt who had proven maximum invasion depth of sm2/sm3, and who in case of ET had a follow-up (FU) by EUS of at least 24 months. 23/38 pt with pT1b sm2 lesions and 39/69 pt with sm3 lesions fulfilled our inclusion criteria. In the pT1b sm2 group, rate of LN metastasis in the hisLR, hisHR, combLR, and combHR groups were 8.3% (1/12), 36.3% (4/11), 0% (0/5), and 27.8% (5/18). In the pT1b sm3 group, rate of LN metastasis in the hisLR, hisHR, combLR and combHR groups were 28.6% (2/7), 37.5% (12/32), 25% (1/4), and 37.1% (13/35). 30-day mortality of surgery was 1.7% (1/58 pt). In EAC with pT1b sm2/3 invasion, the frequency of LN metastasis depends on macroscopic and histological risk patterns. Surgery remains the standard treatment, because the rate of LN metastasis appears to be higher than the mortality risk of surgery. Whether a highly selected group of pT1b sm2 patients with a favourable risk pattern may be candidates for endoscopic therapy cannot be decided until the results of larger case volumes are available.
Gesehen am 17.09.2018
Published: 20 December 2016